Konserwatyzm wobec nurtu ponowoczesności – wzajemne relacje i zależności - Graban, Michał (Civitas. Studia z filozofii polityki, 2014)
The article uses the example of the issue of instrumental reason and enlightened idea of progress to show the similarity between the conservative doctrine and the postmodern thought. It discusses the pessimistic, or even apocalyptic nature of both of these world views as well as their nostalgia for the past. The article also analyzes basic differences in the way the two world views perceive the “metaphysics of presence”. Without denying the importance of these differences, it was proved that the thesis of the “death of God” articulated by postmodernists is not a strong value judgment and only shows the trends of thought in the contemporary world. Moreover, both world views are characterized as longing for the lost “metaphysics of presence”, which shows the possibility of their mutual synthesis, which in turn can be defined as postmodern conservatism.